Charge radii of exotic potassium isotopes challenge nuclear theory and the magic character of N = 32 - Koszorús, Á.; Yang, X. F.; Jiang, W. G.; Novario, S. J.; Bai, S. W.; Billowes, J.; Binnersley, C. L.; Bissell, M. L.; Cocolios, T. E.; Cooper, B. S.; de Groote, R. P.; Ekström, A.; et al. (Nature Physics, 2021)
Nuclear charge radii are sensitive probes of different aspects of the nucleon–nucleon interaction and the bulk properties of nuclear matter, providing a stringent test and challenge for nuclear theory. Experimental evidence suggested a new magic neutron number at N = 32 (refs. 1–3) in the calcium region, whereas the unexpectedly large increases in the charge radii4,5 open new questions about the evolution of nuclear size in neutron-rich systems. By combining the collinear resonance ionization spectroscopy method with β-decay detection, we were able to extend charge radii measurements of potassium isotopes beyond N = 32. Here we provide a charge radius measurement of 52K. It does not show a signature of magic behaviour at N = 32 in potassium. The results are interpreted with two state-of-the-art nuclear theories. The coupled cluster theory reproduces the odd–even variations in charge radii but not the notable increase beyond N = 28. This rise is well captured by Fayans nuclear density functional theory, which, however, overestimates the odd–even staggering effect in charge radii. These findings highlight our limited understanding of the nuclear size of neutron-rich systems, and expose problems that are present in some of the best current models of nuclear theory.
CRIS-Team Scopus Importer:2021-02-05